228‐nm quadrupled quasi‐three‐level Nd:GdVO4 laser for ultraviolet resonance Raman spectroscopy of explosives and biological molecules. (5th October 2020) - Bykov, Sergei V.; Roppel, Ryan D.; Mao, Michael; Asher, Sanford A.
Abstract: We describe a new compact diode‐pumped solid‐state frequency quadrupled quasi‐three‐level neodymium‐doped gadolinium vanadate (Nd:GdVO4 ) laser that generates ~50 mW of 228‐nm quasi‐continuous wave light as ns pulses at a tunable kilohertz repetition rate. We developed two generations of this laser. The first generation has a high duty cycle and a tunable repetition rate. The second generation is optimized for maximum output power. We utilize these new lasers to measure ultraviolet resonance Raman (UVRR) spectra of many important chromophores that absorb in deep ultraviolet (UV). We demonstrate the utility of this excitation by measuring the 228‐nm absolute differential Raman cross sections of explosives, peptides, aromatic amino acids, and DNA/RNA nucleotides. Deep UV excitation at 228 nm occurs within the π → π* electronic transitions of these molecules. The 228‐nm resonance excitation enhances the Raman intensities of vibrations of NO x groups, peptide bonds, aromatic amino acid side chains, and DNA/RNA nucleotides. The measured 228‐nm UVRR cross sections of these molecules are 10 3 –10 4 fold greater than those excited in the visible spectral region. These new lasers should be of great interest for UVRR spectroscopy and for other applications that benefit from compact, high average power deep UV laser light sources with low peak powers. Abstract : We describe a new compact DPSS frequency quadrupled quasi‐three‐level Nd:GdVO4 laser that generates ~50 mW of 228‐nm quasi‐CW light as ns pulses at a tunable kHz repetition rate. We demonstrate the utility of this excitation by measuring the 228‐nm absolute differential Raman cross sections of explosives, peptides, aromatic amino acids, and DNA/RNA nucleotides.